Komunikasi Lintas Budaya dalam Menjaga Kerukunan Antar Umat Beragama - Dahrun, Alfian; Najamuddin, Najamuddin; Alwi, Alimin (Indo-MathEdu Intellectuals Journal, 2025)
Indonesia is known as a multicultural country with a diversity of ethnicities, religions, and cultures that are both a national treasure and a potential source of social conflict. In this context, tolerance and shared awareness are necessary to maintain social harmony. This study aims to describe the role of cross-cultural communication in maintaining religious harmony in RT C BTN AL, Kapasa Village, Tamalanrea District, Makassar City, which is an area with a high level of ethnic and religious diversity. This study uses a qualitative approach with a descriptive method. The results show that cross-cultural communication plays an important role in strengthening social relations and preventing conflicts between religious communities. The values of mutual cooperation, mutual respect, and active participation of residents in social activities such as Independence Day celebrations, RT social gatherings, and solidarity when residents are in mourning are key to maintaining harmony. Thus, cross-cultural communication has proven to be an important instrument in building harmony and strengthening social cohesion in multicultural communities.